Increased deformation of the left ventricle during exercise test measured by global longitudinal strain can rule out significant coronary artery disease in patients with suspected unstable angina pectoris. Issue 2 (18th January 2022) - Karlsen, Sigve; Melichova, Daniela; Dahlslett, Thomas; Grenne, Bjørnar; Sjøli, Benthe; Smiseth, Otto; Edvardsen, Thor; Brunvand, Harald
Abstract: Background: Noninvasive identification of significant coronary artery disease (CAD) in patients with unstable angina pectoris (UAP) is challenging. Exercise stress testing has been used for years in patients with suspected CAD but has low diagnostic accuracy. The use of Global longitudinal strain (GLS) by speckle tracking echocardiography is a highly sensitive and reproducible parameter for detection of myocardial ischemia. Our aim was to study if identification of normal or ischemic myocardium by measurement of GLS immediately after an ordinary bicycle exercise stress testing in patients with suspected UAP could identify or rule out significant CAD. Methods: Seventy‐eight patients referred for coronary angiography from outpatient clinics and the emergency department with chest pain, inconclusive ECG and normal values of Troponin‐T was included. All patients underwent echocardiographic examination at rest and immediately after maximum stress by exercise on a stationary bicycle. Significant CAD was defined by diameter stenosis > 90% by coronary angiography. In patients with coronary stenosis between 50–90%, fractional flow reserve (FFR) was measured and defined abnormal < .80. Analysis of echocardiographic data were performed blinded for angiographic data. Patients were discharged diagnosed with CAD (n = 34) or non‐coronary chest pain (NCCP, n = 44). Results: In patients with NCCP, GLS at rest was ‐21.1 ± 1.7% and ‐25.5 ± 2.6% at maximum stress ( P < .01). In patients with CAD, GLS at rest was ‐16.8 ± 4.0% and remained unchanged at maximum stress (‐16.6 ± 4.6%, P = .69). In patients with NCCP, LVEF was 56.1% ± 6.0 and increased to 61.8% 5.2, P < .01. In CAD patients, LVEF at rest was 54.7% ± 8.6 and increased to 58.2% ± 9.5 during stress, P = .16. In NCCP patients, Wall Motion Score index decreased .02 ± .07, P = .03 during stress and was without significant changes in patients with CAD. Area under the curve (AUC) for distinguishing CAD for was .97 (.95‐1.00), .63 (.49‐.76), and .71 (.59‐.83) for GLS, LVEF, and WMSi, respectively. Conclusion: In patients with suspected UAP, increased deformation of the left ventricle measured by GLS immediately after exercise stress testing identified normal myocardium without CAD. Reduced LV contractile function by GLS without increase after exercise identified significant CAD.